1997
DOI: 10.1136/bmj.315.7115.1060
|View full text |Cite
|
Sign up to set email alerts
|

Acute viral infections of upper respiratory tract in elderly people living in the community: comparative, prospective, population based study of disease burden

Abstract: Objective: To evaluate the disease burden of upper respiratory infections in elderly people living at home. Design: Prospective surveillance of elderly people. Intervention: None. Setting: Leicestershire, England Subjects: 533 subjects 60 to 90 years of age. Main outcome measures: Pathogens, symptoms, restriction of activity, duration of illness, medical consultations, interval between onset of illness and medical consultation, antibiotic use, admission to hospital, and death. Results: 231 pathogens were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
239
3
14

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(280 citation statements)
references
References 23 publications
24
239
3
14
Order By: Relevance
“…Among the respiratory viruses tested for and identified, influenza was dominant (almost 80·0%), which agrees with previous reports relating to the elderly 2 , 11 . In our study, influenza viruses were four times more prevalent than RSV and 35 times more common than hMPV.…”
Section: Discussionsupporting
confidence: 92%
“…Among the respiratory viruses tested for and identified, influenza was dominant (almost 80·0%), which agrees with previous reports relating to the elderly 2 , 11 . In our study, influenza viruses were four times more prevalent than RSV and 35 times more common than hMPV.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, the detection of influenza infection presenting with both fever and cough was observed to have sensitivities ranging between 64 and 86%, specificities between 55 and 67%, and PPVs ranging between 48 and 87% [5,6,19,20]. This contrasts other studies which reported that no clinical signs or symptoms are specific for influenza virus infection [21,22]. The present study indicates that the clinical diagnosis of influenza, based on the combined presence of fever and cough, is difficult among children in everyday clinical practice.…”
Section: Discussionmentioning
confidence: 64%
“…The most relevant virus types include respiratory syncytial viruses, parainfluenza viruses, rhinoviruses, and adenoviruses, among others. 7,12 Thus, vaccination would not protect the population against any airways infection, but only against cases of influenza infection by viruses that are part of the vaccine used in that season. 2 Regarding specific symptoms, fever was rarely reported by subjects, even in the presence of other more frequent respiratory symptoms such as coughing, nose discharge, and sore throat.…”
Section: Discussionmentioning
confidence: 99%